Vocabulary Gains of Mono- and Multilingual Learners in a Linguistically Diverse Setting: Results From a German-English Intervention With Inclusion of Home Languages - Festman, Julia (Frontiers in Communication, 2018)
Today, group settings (e.g., in kindergarten) are more linguistically-diverse than ever. However, concepts in language acquisition only rarely include this fact. This paper reports on the effects of a language intervention which is based on a concept specifically designed for linguistically-diverse settings („PROgramme for BI- and MUltilingual Children“; Festman and Rinker, 2014). The implementation of the programme and its outcomes are described with the example of a German-English-immersion kindergarten, which was in fact plurilingual. We aimed at supporting children’s acquisition of the two languages in parallel with inclusion of their home languages. Overall, 52 (mono-, bi-, and trilingual) children took part in the intervention, although data will only be presented for those children (n = 22; 12 male; mean age 3;9 years, SD 0.526) who also participated in the evaluation. Two weeks before (T1) and 12 weeks after (T2) intense intervention, we administered a word production and word comprehension test (picture naming) both in German and English. Furthermore, parents filled out a questionnaire on language background and use; after the intervention, they provided feedback on the programme (their impressions and observations, etc.). Paired t-tests showed that the intervention noticeably boosted all children’s word learning (all gains from T1 to T2 were significant with p < .001 for both languages and both production and comprehension). With a head start in German (i.e., at T1 significantly higher scores in German comprehension and production), the monolingual German participants (n = 11) reached significantly higher scores in German as well as at T2 compared to their peers. The international group (n = 11) had significantly larger gains in German than their monolingual peers (p =.037 for production; p =.015 for comprehension), but not in English. We conclude that with the help of this structured programme and due to plurilingual experiences, minority children were able to improve language skills in two newly-learned languages, whereas the monolingual children were still consolidating knowledge in their first language and focused on the acquisition of the new language. Parents’ responses described the positive impact of the programme on their children’s language learning interest and their own.